2022
DOI: 10.1038/s41541-022-00513-w
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Mycoplasma pneumoniae membrane lipoproteins induces IL-17A driven neutrophilia that mediates Vaccine-Enhanced Disease

Abstract: Bacterial lipoproteins are an often-underappreciated class of microbe-associated molecular patterns with potent immunomodulatory activity. We previously reported that vaccination of BALB/c mice with Mycoplasma pneumoniae (Mp) lipid-associated membrane proteins (LAMPs) resulted in lipoprotein-dependent vaccine enhanced disease after challenge with virulent Mp, though the immune responses underpinning this phenomenon remain poorly understood. Herein, we report that lipoprotein-induced VED in a mouse model is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…In addition, investigations of CD4 + T cell behavior in mouse models of the related pathogen M. pulmonis revealed a similar decrease in lung pathology after depletion of CD4 + T cells 61 , further implicating Th cells in the dysregulated response. Exposure to M. pneumoniae antigen has been reported to induce the expression of inflammatory cytokines associated with the Th17 lineage, including IL-17A and IL-23 26 , 62 65 , and IL-17A has been shown to exacerbate lung pathology in mice infected with Mycoplasma pulmonis 66 . The Th17/Treg axis is dynamic, and heavily influenced by anti-inflammatory cytokines during T cell exposure to antigen.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, investigations of CD4 + T cell behavior in mouse models of the related pathogen M. pulmonis revealed a similar decrease in lung pathology after depletion of CD4 + T cells 61 , further implicating Th cells in the dysregulated response. Exposure to M. pneumoniae antigen has been reported to induce the expression of inflammatory cytokines associated with the Th17 lineage, including IL-17A and IL-23 26 , 62 65 , and IL-17A has been shown to exacerbate lung pathology in mice infected with Mycoplasma pulmonis 66 . The Th17/Treg axis is dynamic, and heavily influenced by anti-inflammatory cytokines during T cell exposure to antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that IL-17 contributes to the clearance of bacterial pathogens such as Pseudomonas aeruginosa, Klebsiella pneumoniae, and Streptococcus pneumoniae in the respiratory tract [77,78]. During M. haemolytica infection high levels of IL-17 in the lungs can lead to the uncontrolled infiltration of neutrophils and has been attributed to lung damage in mice, goats, and big horn sheep [26,79,80], although IL-17 does not seem to cause any damage in domestic sheep [80]. These studies suggest that IL-17 could help in clearing bacterial pathogens, particularly during early stages of respiratory infection, thus providing mucosal immunity during pneumonia.…”
Section: Plos Onementioning
confidence: 99%
“…Many factors affect the efficacy of the vaccine, including the antigen itself. Some surface lipoproteins can aggravate the disease caused by mycoplasma infection 41 . RS00275 is also a kind of surface lipoprotein.…”
Section: Discussionmentioning
confidence: 99%